2000
DOI: 10.1002/j.2168-9830.2000.tb00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Peer Education in Cooperative Learning Workgroups

Abstract: Many recent studies demonstrate that cooperative learning provides a variety of educational advantages over more traditional instructional models, both in general and specifically in engineering education. Little is known, however, about the interactional dynamics among students in engineering work groups. To explore these dynamics and their implications for engineering education, we analyzed work sessions of student groups in a sophomore‐level chemical engineering course at North Carolina State University. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 9 publications
0
72
0
3
Order By: Relevance
“…For example, while investigating how collaborative peer discussions provided cognitive support for writing laboratory reports, she found that students frequently used peer teaching strategy -either directly imparting information, or facilitating 32 learning for his or her partner‖ (p. 182). Haller et al (2000) also observed a similar interactional feature among sophomores while they were collaboratively solving their engineering problems in groups. Their findings show interesting dynamics of peer interaction that result from asymmetrical distribution of knowledge and technical expertise in the group.…”
Section: Discussionmentioning
confidence: 60%
“…For example, while investigating how collaborative peer discussions provided cognitive support for writing laboratory reports, she found that students frequently used peer teaching strategy -either directly imparting information, or facilitating 32 learning for his or her partner‖ (p. 182). Haller et al (2000) also observed a similar interactional feature among sophomores while they were collaboratively solving their engineering problems in groups. Their findings show interesting dynamics of peer interaction that result from asymmetrical distribution of knowledge and technical expertise in the group.…”
Section: Discussionmentioning
confidence: 60%
“…While some studies analyze student profiles in order to build ideal groups and improve group performance (Durán, 2006), and others issue recommendations based on different variables (Haller et al, 2000), our project decided to charge professors with assembling work pairs rather randomly, instead of having students deciding who they would like to work with. In general, participants report good group coordination and a good experience in this regard too.…”
Section: Resultsmentioning
confidence: 99%
“…Ghazi's work shows that teachers' experience is not related to their willingness to implement STAD, but their teaching rationale is. If a researcher assumes the role of a tutor, motivational experiences may perhaps be more accessible (Haller, Gallagher, Weldon & Felder, 2000). …”
Section: The Implications Of the Research Findingsmentioning
confidence: 99%